2008
DOI: 10.1210/jc.2007-1853
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of the Adipokine Vaspin in Relation to Metabolic and Renal Parameters

Abstract: Vaspin levels are significantly higher in women, and gender is an independent predictor of circulating vaspin in both control and CD patients. In addition, age independently predicts vaspin in control patients, whereas GFR and CRP are independently associated with this adipokine in CD patients. In contrast, circulating vaspin is not independently associated with markers of glucose and lipid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
102
3
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 15 publications
19
102
3
6
Order By: Relevance
“…The h 2 of 0.78 suggests a major influence of genetic factors in women and thus sexual dimorphism in the heritability of serum vaspin levels. Interestingly, a sex difference in circulating vaspin levels was also found in previous studies, reporting elevated vaspin concentrations in female compared with male participants [3,4]. In conclusion, our results indicate that, in vivo, serum vaspin levels are elevated in individuals with IFG/IGT and type 2 diabetes.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The h 2 of 0.78 suggests a major influence of genetic factors in women and thus sexual dimorphism in the heritability of serum vaspin levels. Interestingly, a sex difference in circulating vaspin levels was also found in previous studies, reporting elevated vaspin concentrations in female compared with male participants [3,4]. In conclusion, our results indicate that, in vivo, serum vaspin levels are elevated in individuals with IFG/IGT and type 2 diabetes.…”
supporting
confidence: 87%
“…
Abbreviations
DZHowever, in humans the association between serum vaspin levels and obesity variables is conflicting [3,4], and the relationship between circulating vaspin levels and glucose metabolism remains controversial [5,6]. In addition to these issues, it is still unknown whether serum vaspin levels are influenced by genetic or environmental factors.
…”
mentioning
confidence: 99%
“…Besides expression in WAT, we identified vaspin mRNA expression in the liver and potentially in the skin and the pancreas. Most studies found higher vaspin levels in adult women compared with men, 6,8,[16][17][18] whereas others did not. 7,9,19 According to our data, vaspin increased with puberty in girls, but not in boys.…”
Section: Discussionmentioning
confidence: 99%
“…1 It was concluded that elevated vaspin may be a compensatory response to insulin resistance secondary to the metabolic complications of obesity. 3 In humans, some subsequent studies confirmed the association of vaspin with obesity and BMI, 4,5 although the association was more subtle 6 or absent 7,8 in other studies. Several studies found a positive correlation of circulating vaspin with insulin resistance indices 5,9,10 but not with the presence of overt type 2 diabetes.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation